Education and Obesity in Four OECD Countries - Sassi, Franco (OECD Publishing, 2009)
An epidemic of obesity has been developing in virtually all OECD countries over the last 30 years. Existing evidence provides strong suggestions that such epidemic has affected certain social groups more than others. In particular, education appears to be associated with a lower likelihood of obesity, especially among women. A range of analyses of health survey data from Australia, Canada, England and Korea were undertaken with the aim of exploring the relationship between education and obesity. The findings of these analyses show a broadly linear relationship between the number of years spent in full-time education and the probability of obesity, with most educated individuals displaying lower rates of the condition (the only exception being men in Korea). This suggests that marginal returns to education, in terms of reduction in obesity rates, are approximately constant throughout the education spectrum.
Keywords: Education